Efficacy and safety of transjugular intrahepatic portosystemic shunt (TIPSS) in 40 patients with hepatocellular carcinoma. Issue 1 (20th October 2014) - Bettinger, D.; Knüppel, E.; Euringer, W.; Spangenberg, H. C.; Rössle, M.; Thimme, R.; Schultheiß, M.
Summary Background Portal hypertension and hepatocellular carcinoma (HCC) are major complications of advanced liver cirrhosis. Thus, patients are often affected by both complications. Transjugular intrahepatic portosystemic shunt (TIPSS) is an effective treatment for portal hypertension and its complications. However, no established guidelines for the treatment of symptomatic portal hypertension in HCC patients are currently available. In addition, only limited information exists about the consequence of TIPSS implantation in patients with HCC. Aim To evaluate the efficacy, safety and overall survival in HCC patients who underwent TIPSS implantation. Methods Forty HCC patients with portal hypertension who were treated with TIPSS between 1995 and 2012 were included in the analysis. Medical records and imaging studies were analysed. The indication for TIPSS implantation, procedure‐related complications, treatment success and overall survival were assessed. Results TIPSS implantation was performed in 23 patients (57.5%) due to treatment refractory ascites, in 14 patients (35.0%) due to recurrent variceal bleeding and in three patients (7.5%) due to ascites and variceal bleeding. Primary technical success was assessed in all patients. After TIPSS implantation, no variceal bleeding reoccurred and ascites was controlled in 74.1%. No severe procedure‐related complications and no deterioration of liver function were observed. Post‐TIPSS hepatic encephalopathy occurred in 40.0% of all patients. 30‐day, 90‐day‐, 1‐year‐ and 5‐year survival rates were 97.5%, 75.0%, 42.5% and 7.5%, respectively. Median overall survival after TIPSS implantation was 180 days. Conclusion Transjugular intrahepatic portosystemic shunt implantation is an effective and safe treatment for portal hypertension in patients with HCC.